2019
DOI: 10.1016/j.neuron.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Deficiency Reduces Striatal Cholinergic Interneuron Function in Models of Parkinson’s Disease

Abstract: Motor and cognitive functions depend on the coordinated interactions between dopamine (DA) and acetylcholine (ACh) at striatal synapses. Increased ACh availability was assumed to accompany DA deficiency based on the outcome of pharmacological treatments and measurements in animals that were critically depleted of DA. Using Slc6a3 DTR/+ diphtheria-toxin-sensitive mice, we demonstrate that a progressive and L-dopa-responsive DA deficiency reduces ACh availability and the transcription of hyperpolarization-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
114
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 70 publications
14
114
1
Order By: Relevance
“…ChIs exhibit cell autonomous firing patterns, including irregular firing with bursts and pauses (Goldberg and Wilson, 2005;Wilson, 2005;Wilson and Goldberg, 2006). Previous reports showed that DA depletion decreased the regularity of spontaneous firing and the number of bursts and pauses (McKinley et al, 2019). Consistent with these findings, we found an increase in the coefficient of variation (CV) of the instantaneous frequencies of sAP in ChIs from 6-OHDA mice, which was restored to sham control levels after chronic L-DOPA (Figure 1D).…”
Section: Changes In Chi Spontaneous Firing Rate Following Da Depletiosupporting
confidence: 90%
See 1 more Smart Citation
“…ChIs exhibit cell autonomous firing patterns, including irregular firing with bursts and pauses (Goldberg and Wilson, 2005;Wilson, 2005;Wilson and Goldberg, 2006). Previous reports showed that DA depletion decreased the regularity of spontaneous firing and the number of bursts and pauses (McKinley et al, 2019). Consistent with these findings, we found an increase in the coefficient of variation (CV) of the instantaneous frequencies of sAP in ChIs from 6-OHDA mice, which was restored to sham control levels after chronic L-DOPA (Figure 1D).…”
Section: Changes In Chi Spontaneous Firing Rate Following Da Depletiosupporting
confidence: 90%
“…Similarly, increasing ChI firing rate by chemogenetic or optogenetic methods enhanced LID expression (Aldrin-Kirk et al, 2018;Bordia et al, 2016a), while decreasing ChI firing rate by inhibiting H2 histamine receptors that are preferentially expressed in ChIs in the striatum, attenuated LID (Lim et al, 2015). Alterations in ChI activity following DA depletion have been studied, although with conflicting results (Ding et al, 2006;Maurice et al, 2015;McKinley et al, 2019;Sanchez et al, 2011;Tubert et al, 2016). However, the basis of changes in ChI physiology resulting from chronic L-DOPA treatment of DA depleted mice have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Shh binding to Ptc1 relieves the inhibition of Smo [42]. [8], target CIN of the DLS [44] and degenerate in PD [32]. We found that mice with selective ablation of Shh from DAN (ShhDAN -/- [8] ShhDAN -/mice resulted in an increase in the fraction of pErk 1,2 positive CIN in the DLS, which could be normalized by SAG ( Fig.…”
Section: B)mentioning
confidence: 93%
“…Unfortunately, how DAN degeneration results in aberrant CIN activity is also not well understood [30]. For example, as DA levels fall in the PD brain, cholinergic signaling strength rises [31], yet acetylcholine availability becomes reduced concomitantly with progressive DAN deficiency in murine models [32] suggesting that relative rather than absolute levels of cholinergic tone might change in PD.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation